Children exploitation in John Burnside's The Dumb House - Aldhafeeri, Hilalah; Ali Termizi, Arbaayah (American Research Institute for Policy Development, 2015)
This article examines the interdisciplinary ecocriticism in John Burnside’s The Dumb House (1997). The study focuses on two critical perspectives. The first of these is ecocriticism. The main focus will be on two ecocritical concepts, dwelling and ecoconsciousness. The concept of dwelling will be mainly addressed by referring to Greg Garrard’s postulation of dwelling and using it to analyze natural settings in fictional works. Dwelling, therefore, will be applied to analyze the novel’s setting. Second, using ecoconsciousness, the analysis will draw on Cheryll Glotfelty’s formulation of ecoconsciousness and its critical interface with other interdisciplinary approaches. Psychoanalysis will be the interdisciplinary method used, along with dwelling and ecoconsciousness. Sigmund Freud’s concept of anxiety is the sole psychoanalytical concept that will be used in this study. Considering anxiety reveals the novel’s protagonist’s inner feelings, caused by repression and remembering the past. Thus the novel’s natural setting is a remedial exit for the protagonist’s anxiety.